2016
DOI: 10.3748/wjg.v22.i32.7353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different diets on intestinal microbiota and nonalcoholic fatty liver disease development

Abstract: Compared with the high-protein diet, the NAFLD-inducing effects of high-fat and high-sugar diets are independent from calories, and may be associated with changed intestinal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 48 publications
7
44
1
Order By: Relevance
“…The predicted PCoA exhibited partial clustering of CF and BARF groups (P value < 0.01), supporting the notion that the two distinct diets indeed cause differences in the canine gut microbiota. can also metabolize a wide range of different carbohydrates (Lopez-Siles et al, 2012;Liu et al, 2016). Specifically, Fusobacteria and Actinobacteria were significantly increased in dogs fed on a BARF diet, while Bacteroidetes showed an opposite trend ( Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The predicted PCoA exhibited partial clustering of CF and BARF groups (P value < 0.01), supporting the notion that the two distinct diets indeed cause differences in the canine gut microbiota. can also metabolize a wide range of different carbohydrates (Lopez-Siles et al, 2012;Liu et al, 2016). Specifically, Fusobacteria and Actinobacteria were significantly increased in dogs fed on a BARF diet, while Bacteroidetes showed an opposite trend ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…and Sutterella spp. can also metabolize a wide range of different carbohydrates (Lopez-Siles et al, 2012;Liu et al, 2016). Therefore, dogs fed with commercial pet foods, which are typically enriched in fibres and carbohydrates, are associated with a higher abundance of these saccharolytic species, as compared with dogs of the BARF group whose diet was based on a high abundance of animal proteins and fats.…”
Section: Role Of Diet As Modulator Of the Canine Core Gut Microbiotamentioning
confidence: 99%
“…A recent study assessing the impact of iso‐caloric high‐fat, high‐sugar and high‐protein diets, as well as an unlimited high‐fat intake diet, upon the development of NAFLD in rats, showed that diets high in fat and sugar were detrimental to health. The authors also examined the effects of these diets upon gut microbiota composition . Rats fed a high‐fat diet (restricted and unrestricted calorie intake) had higher portal LPS levels than the other dietary groups.…”
Section: The Gut–liver–brain Axis In Cirrhosismentioning
confidence: 99%
“…It was postulated that high‐fat and high‐sugar diets impact upon development of NAFLD, independently of caloric intake and alter the gut flora in different ways. The beneficial effects of a high protein diet may relate to increased levels of Prevotella and Oscillospira …”
Section: The Gut–liver–brain Axis In Cirrhosismentioning
confidence: 99%
“…Adipose tissue releases cytokines to increase inflammation and fibrosis. Gut microbiota is also believed to play a role in the development of NASH via alterations in the BA pool level and composition (Jiang et al, 2015; Liu et al, 2016b; Mei et al, 2015; Wang et al, 2016). Recently, vitamin D deficiency has been proposed as another possible factor as mice fed a high fat diet (HFD) exhibited increased steatosis and hepatic ballooning when coupled with a vitamin D deficiency (Kong et al, 2014).…”
Section: Nafld and Nashmentioning
confidence: 99%